OPTIMISTIC VIEW OF LIFE IN ELEANOR H. PORTER’S POLLYANNA (1913) - Rida Fahas (Al-Lubab : Jurnal Penelitian Pendidikan dan Keagamaan Islam, 2016)
The major problem of this study is the optimistic view of life reflected in Eleanor Porter’s Pollyanna (1913). The aims of this study are to describe Pollyanna portrayal in Eleanor H. Porter’s Pollyanna novel, to explain Pollyanna’s self-concept in novel, and to describe needs and motives underlie Pollyanna’s behavior. This study focuses on the major character, namely Pollyanna. The type of the study is qualitative research. The method of data collection is documentation, while the technique of data analysis is descriptive analysis. The result of this study shows the following conclusion. Firstly, based on the portrayal analysis of Pollyanna, the researcher concludes that Pollyanna as the major character in this novel has flat character. Pollyanna’s character has one side of personality, namely positive. From the beginning of the story until the end of the story, Pollyanna’s personal identity, physical qualities, moral qualities, mental qualities, and social qualities are positive. Secondly, based on humanistic psychological analysis of Carl Rogers, Eleanor H. Porter’s Pollyanna novel shows that the major character, Pollyanna, builds positive self concept. Thirdly, based on humanistic psychological analysis of Abraham Maslow, Pollyanna’s behavior generally is based on belongingness and love needs.  Key words: optimistic, view of life, Pollyanna, Humanistic Psychology